Efficacy of 24-Week Pegylated Interferon Alpha and Ribavirin Combination Therapy in Highly Selected Patients Infected With Hepatitis C Virus Genotype 1 - Sharafi, Heidar (Hepat Mon, 2015)
BACKGROUND: Previous studies using pegylated interferon (Peg-IFN) and ribavirin (RBV) combination therapy suggested that patients with hepatitis C virus (HCV) genotype 1 and low pretreatment HCV RNA level who achieved rapid virological response (RVR) can be treated for 24 weeks without compromising sustained virological response (SVR) rate. OBJECTIVES: The current study aimed to investigate the efficacy of Peg-IFN-alfa-2a plus RBV administered for a 24-week treatment course in patients with chronic HCV genotype 1 infection and possessing the following criteria: low baseline serum HCV RNA level, absence of significant fibrosis and achievement of RVR. PATIENTS AND METHODS: In this case-control study, 20 patients with HCV genotype 1 infection and favorable baseline characteristics and on-treatment response were treated with Peg-IFN and RBV for 24 weeks as the case group. Furthermore, 23 patients with the same characteristics who underwent a 48-week treatment course were selected as the control group. RESULTS: The majority of patients had no fibrosis on liver elastography. There was no statistical difference regarding age, gender, alanine transaminase (ALT) level, rs12979860 polymorphism and the level of fibrosis between the two studied groups. All patients in the 24-week treatment course achieved SVR and all the subjects who received the 48-week treatment course achieved SVR as well (P > 0.99). CONCLUSIONS: The current study confirmed that the efficacy of a 24-week regimen of Peg-IFN-alfa-2a plus RBV was similar to the 48-week treatment in the patients infected with HCV genotype 1, and low baseline HCV RNA level who achieved RVR. Response guided therapy can be efficient and cost-effective among the selected HCV genotype 1-infected patients.